Hubungan Beban Kerja Dan Lama Masa Kerja Dengan Stres Pada Perawat Di Ruang Perawatan 2 RSUD RA. Basuni Gedeg Mojokerto - Fitria Mei Rukmala Dewi (MEDICA MAJAPAHIT, 2012)
Nurses working in hospitals with high workloads and longer working lives are less able to increase the likelihood of job stres, level of stres in nurses was still very high in his job. The study was conducted to determine whether there is a relationship of workload and length of service with nurse stres. The study design used was cross sectional with the technique of sampling with a sampling of the total number of 27 respondents. Location of this research at two hospitals RA.Basuni Perawataan space Kec. Gedeg Mojokerto regency. The population in this study were all nurses at two hospitals RA treatment room. Basuni Kec. Gedeg Kab. Mojokerto. The data was collected using a closed questionnaire. The research was conducted in May 2011. The results showed that the majority of nurses light workload was associated with levels of stres are as many as seven respondents (25.9%). And a long relationship working> 1 year was associated with stres levels as much as 7 respondents (25.9%). Analysis of data using Spearman Rank test workload calculation results obtained with the stres p = 0.007 whereas the value of Î± = 0.05 then there is a relationship work load with stres in nurses, while the length of service with a stres value of p = 0.015 while Î± = 0.05 then there is a link length of service with the stres on caregivers. Workload experienced by the respondents is lighter workload and longer working lives of over one years raises the stress level is. It is influenced by the workplace, saturation levels, job placement and age. Nurses are expected to further enhance the knowledge and work experience so as to reduce the workload and stres levels.